Improving Students' Understanding of Fasting Material Through Discovery Learning Method at Kajhu Elementary School - Sunarti (Jurnal Profesi Guru Indonesia, 2024)
The purpose of this research is to find out the improvement of the ability of class VI students in Mater Puasa with the Discovery Learning learning model. The method used in this research is the Class Action Research (PTK) method. This method is done with four stages, namely planning, action, observation, and reflection. The four levels are found in a cycle that is repeated with the same steps and remains focused on how to solve problems (answers) by finding on your own, researching on your own and searching for information using the discovery learning learning model. The results of this research show that the learning performance of students using this discovery learning method has improved. The improvement can be seen from the results of each cycle performed. The subjects in this research are VI class students of SD Negeri Kajhu who did not reach the KKM value consisting of 2 females and 5 males with a total of 7 students, data collection techniques through observation instruments, teacher activities, student activities and tests. The results of the research show that the teacher's activity in cycle I with an average value of 2.9 categories is good, in cycle II with an average value of 3.7 categories is very good. The activity of students in cycle I obtained the classical completion of only 40% with an average value of 60 categories is not good, while in cycle II the classical completion has reached 90% and the average value of 90 categories is very good. From the results, it is proved that the sixth grade students of SD Negeri Kajhu in the application of the discovery learning learning model can improve the learning outcomes of students in the cognitive domain.